MINORITAS MUSLIM DI NEGARA KOMUNIS LAOS: PERKEMBANGAN DALAM KETERBATASAN - Fikri Surya Pratama (Turast: Jurnal Penelitian dan Pengabdian, 2022)
The general statement is that minority groups have always been discriminated against by the majority, plus Laos itself carries out communism as the state ideology. In general, the discourse on the equality of communists with atheists is quite popular in the community. Not only labeled as having no religion, a state labeled as communist is synonymous with not supporting the existence of an ethnicity or a religious community. This article aims to explain the history and life of Muslim groups in Laos as a minority community group. This research is a historical research, where in collecting data sources using literature study techniques, and data analysis using a political history approach. The results of the study show that Laos, which is geographically located in the middle of mainland Indochina, makes it a crossroads of culture and religion. The political turmoil in the Indochina region and the civil war in Laos had an impact on the number of Laos' Muslim population. Pathet Lao's victory over the civil war resulted in an authoritarian communist government, causing the Muslim population to shrink. The 1991 Lao Constitution amendment in 2003 brought a breath of fresh air with religious freedom to the Lao people. Although there are still problems with human and financial resources in developing the community and da'wah, Laotian Muslims live quietly in a communist country. Islam in Laos is developing slowly but quietly within its limitations.